Penerapan Metode Prototyping Pada Perancangan Sistem Layanan Pengaduan Berbasis Website - Rima Tamara Aldisa; Afif Arofi (STMIK Budi Darma, 2022)
Complaints are submissions in providing suggestions, complaints, reports on events, circumstances and conditions that are not in accordance with standards and regulations. the goals and interests of system users here, the community is an important priority for updating better services for the future, system user satisfaction is needed by the relevant agency or company to provide maximum service. With the creation of this system, it is intended that system users have no difficulty in making complaints or reporting on events that have occurred. By designing a complaint service system with the prototyping method so that system users can immediately make complaints, reports and do not have to come directly to the agency or company. This website will follow up on problems that have occurred and will be given status information whether it has been resolved or not.